2023
DOI: 10.1111/eci.14101
|View full text |Cite
|
Sign up to set email alerts
|

Association between exposure to air pollution and blood lipids in the general population of Spain

Sergio Valdés,
Viyey Doulatram‐Gamgaram,
Cristina Maldonado‐Araque
et al.

Abstract: Background and AimsWe aimed to assess the associations of exposure to air pollutants and standard and advanced lipoprotein measures, in a nationwide sample representative of the adult population of Spain.MethodsWe included 4647 adults (>18 years), participants in the national, cross‐sectional, population‐based di@bet.es study, conducted in 2008–2010. Standard lipid measurements were analysed on an Architect C8000 Analyzer (Abbott Laboratories SA). Lipoprotein analysis was made by an advanced 1H‐NMR lipoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…A considerable amount of accumulating research suggested that long-term exposure to fine particulate matter (PM 2.5 ) is connected to an elevated likelihood of developing CVD ( 8 , 9 ). Based on biological plausibility, it is conceivable that prolonged exposure to air pollution, through the aforementioned mechanistic pathways, might induce undesirable alterations in CVD risk factors, encompassing blood lipid, glucose, and Hcy levels ( 10 , 11 ). Consequently, these modifications could serve as intermediaries connecting exposures to the overt manifestation of CVD ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable amount of accumulating research suggested that long-term exposure to fine particulate matter (PM 2.5 ) is connected to an elevated likelihood of developing CVD ( 8 , 9 ). Based on biological plausibility, it is conceivable that prolonged exposure to air pollution, through the aforementioned mechanistic pathways, might induce undesirable alterations in CVD risk factors, encompassing blood lipid, glucose, and Hcy levels ( 10 , 11 ). Consequently, these modifications could serve as intermediaries connecting exposures to the overt manifestation of CVD ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%